(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we initiate the study of Set-Domination in the Sub-Division graph of a graph The Sub-division graph of a graph is a graph obtained from by inserting a vertex of degree two for each edge of Let be a Sub-division graph. A Set is a Set-dominating set (Sd-set) of if, for every subset there exists a non-empty subset such that the graph is connected. The Set-Domination number of G is the minimum cardinality of an SD-set. Here we find Set Domination number of Subdivision graphs of some standard graphs and specifically subdivision graph of a non-trivial tree and create comparative inequalities between and other domination parameter of the graph